Polypharmacy: a challenge for the primary health care of the Brazilian Unified Health System - Renata Cristina Rezende Macedo do Nascimento; Juliana Álvares; Augusto Afonso Guerra Junior; Isabel Cristina Gomes; Micheline Rosa Silveira; Ediná Alves Costa; Silvana Nair Leite; Karen Sarmento Costa; Orlando Mario Soeiro; Ione Aquemi Guibu; Margô Gomes de Oliveira Karnikowski; Francisco de Assis Acurcio (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To characterize the polypharmacy in primary health care patients and to identify its associated factors. METHODS This is a cross-sectional, exploratory, and evaluative study, part of the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos - Serviços, 2015 (PNAUM - National Survey on Access, Use and Promotion of Rational Use of Medicines - Services, 2015). The variable of interest was polypharmacy, defined as the use of five or more medicines. We sought to identify the association of sociodemographic variables and indicators of health conditions to polypharmacy. For group comparison, the Pearson's Chi-square test was used. The association between polypharmacy and explanatory variables was evaluated by logistic regression model (p < 0.05). The quality of the adjustment was verified by Hosmer-Lemeshow test. RESULTS The prevalence of polypharmacy among medicine users was 9.4% (95%CI 7.8-12.0) in the general population and 18.1% (95%CI 13.6-22.8) in older adults above 65 years old. We found statistically significant association between polypharmacy and age above 45 years, lower self-perception of health, presence of chronic diseases, having health insurance, care in emergency services, and region of the Country. South users presented the highest chances to polypharmacy. The most used medicines were those of the cardiovascular system, being compatible with the national epidemiological profile. CONCLUSIONS Polypharmacy is a reality in the population met within the primary care of Brazilian Unified Health System and may be related to excessive or inappropriate use of medicines. The main challenge to qualify health care is to ensure that prescription of multiple medicines be appropriate and safe.